Assessment of Aquatic Macroinvetebrate and Physio-Chemical Parameters in River Donga, Donga, Taraba State, Nigeria - Winifred, Ronald Abhulimen; Flourizel, Igbani; Rachael, Iba Nguwasen (Darul Yasin Al Sys, 2024)
This study assessed the diversity of macroinvertebrates fauna and water quality parameters in river donga. Soil and water samples were randomly collected in the months of September and November, 2022 at three different locations: Headwater (Point A), middle water or Polo (Point B) and tailwater or Spillway (Point C) in the river. The following phylum of macro-invertebrates were reported, Arthropoda and Mollusca. The species present were, Viviparous viviparous, Sadleriana fluminensis, Velia caprai, Mytilus edulis. The temperature ranges between 26.67±0.35 to 27.17±0.35 with the middle point and Tail water point having the lowest and highest temperatures respectively. PH values ranges from 6.97±0.01 to 7.04±1.55 with the headwater point and Middle water point having the lowest and highest temperatures respectively. Electrical conductivity (Mg/l) values ranges between 263.33±6.52 to 280.00±8.65 with Tail water and Middle water having the lowest and highest concentrations respectively. Dissolved oxygen concentration ranges between 5.57±0.20 to 5.97±0.53 with headwater and tail water having the lowest and highest dissolved oxygen. There was however no significant difference in the evaluated parameters water parameter (p≤0.05). All water quality parameters except Electrical conductivity and Dissolved oxygen were slightly above WHO limits of all the evaluated water parameters. Diversity index indicated Head of the sampling locations was more diverse than all other sampling site along river Donga. The present study revealed that Donga River is not polluted as indicated by the abundance of pollution intolerant macro-invertebrate species and the physiochemical parameters of water. The water quality parameters evaluated were favourable and is a clear indication of good water quality. However, findings from the present study revealed the presence of few macro-invertebrates at the study location. This could be attributed to uneven specie distribution in nature. Another factor could be due to duration, season and the sampling locations along the Donga River. It has given us the baseline study of macroinvertebrates present in Donga River and also the water quality of the river.